Volume of interest-based fractal analysis of Huffaz’s Brain - Jamaludin, Iqbal; Che Azemin, Mohd Zulfaezal; Mohd Tamrin, Mohd Izzuddin; Sapuan, Abdul HaliM (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The robust process in memorising the Quran is expected to cause neuroplasticity changes in the brain. To date, the analysis of neuroplasticity is limited in binary images because greyscale analysis requires the usage of more robust processing techniques. This research work aims to explore and characterise the complexity of textual memorisation brain structures using fractal analysis between huffaz and non-huffaz applying global box-counting, global Fourier fractal dimension (FFD), and volume of interest (VOI)-based analysis. The study recruited 47 participants from IIUM Kuantan Campus. The huffaz group had their 18 months of systematic memorisation training. The brain images were acquired by using MRI. Global box-counting and FFD analysis were conducted on the brain. Magnetic resonance imaging (MRI) found no significant statistical difference between brains of huffaz and non-huffaz. VOI-based analysis found nine significant areas: two for box-counting analysis (angular gyrus and medial temporal gyrus), six for FFD analysis (BA20, BA30, anterior cingulate, fusiform gyrus, inferior temporal gyrus, and frontal lobe), and only a single area (BA33) showed significant volume differences between huffaz and non huffaz. The results have highlighted the sensitivity of VOI based analysis because of its local nature, as compared to the global analysis by box-counting and FFD.